Sucrose Transporter Localization and Function in Phloem Unloading in Developing Stems. Issue 2 (16th December 2016) - Milne, Ricky J.; Perroux, Jai M.; Rae, Anne L.; Reinders, Anke; Ward, John M.; Offler, Christina E.; Patrick, John W.; Grof, Christopher P.L.
Abstract : Sorghum sucrose transporters may function to efflux sucrose from the phloem during early internode development and retrieve leaked sucrose to the phloem as internodes mature. Abstract: How sucrose transporters (SUTs) regulate phloem unloading in monocot stems is poorly understood and particularly so for species storing high Suc concentrations. To this end, Sorghum bicolor SUTs SbSUT1 and SbSUT5 were characterized by determining their transport properties heterologously expressed in yeast or Xenopus laevis oocytes, and their in planta cellular and subcellular localization. The plasma membrane-localized SbSUT1 and SbSUT5 exhibited a strong selectivity for Suc and high Suc affinities in X. laevis oocytes at pH 5—SbSUT1, 6.3 ± 0.7 mm, and SbSUT5, 2.4 ± 0.5 mm Suc. The Suc affinity of SbSUT1 was dependent on membrane potential and pH. In contrast, SbSUT5 Suc affinity was independent of membrane potential and pH but supported high transport rates at neutral pH. Suc transport by the tonoplast localized SbSUT4 could not be detected using yeast or X. laevis oocytes. Across internode development, SUTs, other than SbSUT4, were immunolocalized to sieve elements, while for elongating and recently elongated internodes, SUTs also were detected in storage parenchyma cells. We conclude that apoplasmic Suc unloading from de-energized protophloem sieve elements in meristematic zones may be mediated by reversal of SbSUT1 and/or by uniporting SWEETs. Storage parenchyma localized SbSUT1 and SbSUT5 may accumulate Suc from the stem apoplasms of elongating and recently elongated internodes, whereas SbSUT4 may function to release Suc from vacuoles. Transiting from an apoplasmic to symplasmic unloading pathway as the stem matures, SbSUT1 and SbSUT5 increasingly function in Suc retrieval into metaphloem sieve elements to maintain a high turgor to drive symplasmic unloading by bulk flow.